Isothermal and non-isothermal kinetic study on CO2 gasification of torrefied forest residues. (August 2016) - Tran, Khanh-Quang; Bui, Hau-Huu; Luengnaruemitchai, Apanee; Wang, Liang; Skreiberg, Øyvind
Abstract: CO2 gasification of torrefied forest residues (birch and spruce branches) was investigated by means of a thermogravimetric analyser operated non-isothermally (400–1273 K) and isothermally (1123 K) under the kinetic regime, followed by kinetic analyses assuming different models. For the non-isothermal gasification, the distributed activation energy model (DAEM) with four or five pseudo-components was assumed. It is found that the severity level of torrefaction had great influences on gasification behaviour as well as devolatilization step. The activation energy of non-isothermal gasification step of three samples varied in the range of 260–290 kJ/mol. The char reactivity decreased with increased torrefaction temperature. For the isothermal gasification, the random pore model (RPM), shrinking core model (SCM), and homogeneous model (HM) were tested. The result has confirmed the trend of decrease in char reactivity with increased torrefaction temperature observed from the non-isothermal gasification. However, different trends in char reactivity due to different wood types were observed by the two methods of gasification. Highlights: Simultaneous non-isothermal and isothermal gasification kinetic studies. DAEM with four or five pseudo-components assumed. Clarification of the formation of lignin-like compound. Char gasification reactivity decreases with increased torrefaction temperature. Reactivity of hardwood char seems higher than softwood char.